THE PERCULIARITIES OF THE FORMATION OF TEMPORARY TEETH OCCLUSION IN CHILDREN, BORN FROM THE MOTHERS IN THE “RISK GROUP” - A. Y. Sydorenko (Український стоматологічний альманах, 2018)
Epidemiological studies of dentofacial anomalies carried out during the last 40 years witness high level of the dentofacial system pathology development. During these years pathology of dentofacial system keeps developing in Ukraine and abroad.